Reprogramming of Tumor-Associated Macrophages with Anticancer Therapies: Radiotherapy versus Chemo- and Immunotherapies - Genard, Géraldine; Lucas, Stéphane; Michiels, Carine (Frontiers in Immunology, 2017)
Tumor-associated macrophages (TAMs) play a central role in tumor progression, metastasis and recurrence after treatment. Macrophage plasticity and diversity allow their classification along a M1 – M2 polarization axis. Tumor–associated macrophages usually display a M2-like phenotype, associated with pro-tumoral features whereas M1 macrophages exert anti-tumor functions. Targeting the reprogramming of TAMs towards M1-like macrophages would thus be an efficient way to promote tumor regression. This can be achieved through therapies including chemotherapy, immunotherapy and radiotherapy. In this review, we first describe how chemo- and immuno-therapies can target TAMs and secondly we detail how radiotherapy modifies macrophage phenotype and present the molecular pathways that may be involved. The identification of irradiation dose inducing macrophage reprogramming and of the underlying mechanisms could lead to the design of novel therapeutic strategies and improve synergy in combined treatments.